System zarządzania ryzykiem - Panasiewicz, Agnieszka (System of risk management, 2008)
The business is still developing and also the aspiration of people to aim more and more benefits give the occassion to set a number of the new impendences – particularly those are unknown till now. The all kind of people activity can bring into any risk. The risk is an impedency not only for people health and their life, but also for the activity is leading by them and for the nature is surrounding them. The process of the risk management includes two phase as below: Phase of the risk analysis − this is an analytic part of the all process. 1. Phase of the risk inspection (management, manipulation - procedure) − this part of the process 2. let to take decission on „how to reduce or eliminate existing impedency and how to finanse the cost of that undertaking?”.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 176-184